Taking Southeast Asia to Market : Commodities, Nature, and People in the Neoliberal Age - Peluso, Nancy Lee; Nevins, Joseph (Book collections on Project MUSE., 2008)
Recent changes in the global economy and in Southeast Asian national political economies have led to new forms of commodity production and new commodities. Using insights from political economy and commodity studies, the essays in Taking Southeast Asia to Market trace the myriad ways recent alignments among producers, distributors, and consumers are affecting people and nature throughout the region. In case studies ranging from coffee and hardwood products to mushroom pickers and Vietnamese factory workers, the authors detail the Southeast Asian articulations of these processes while also discussing the broader implications of these shifts. Taken together, the cases show how commodities illuminate the convergence of changing social forces in Southeast Asia today, as they transform the terms, practices, and experiences of everyday life and politics in the global economy.